Densidade de Alojamento e bem-Estar de Codornas Japonesas em Postura. - Medeiros, Raqueline da Silva (Universidade Federal do Tocantins, 2023)
Coturniculture is a good alternative for the production of animal protein and high densities has been adopted as a way to reduce costs and equipment per bird. However, the excessive reduction of available area by bird can cause stress problems caused by competition for space and food. In this context, it is noticed that consumers have been more demanding in the matter that prioritize the welfare of the animals in all the stages of the productive chain, meat and egg, mainly those of the security and food quality. Thus, well-being is usually the opposite, that is, coming from the outside to the inside, for it expresses itself first in society; which increasingly requires such practices to be applied.